Evaluating the Effect of Forage Rape (Brassica napus) Ensiling Kinetics on Degradability and Milk Performance as Non-conventional Forage for Dairy Buffalo - Abdelrahman, Mohamed; Wang, Wei; Lv, HaiMiao; Di, Zhou; An, Zhigao; Lijun, Wang; Shaukat, Aftab; Bo, Wang; Guangsheng, Zhou; Liguo, Yang; Guohua, Hua (Frontiers in Veterinary Science, 2022)
The recent increase in demand for animal protein sources has led to the urgency to introduce non-conventional feed sources and opened the space to study feed management and its effects on animal productivity. Forage rape (Brassica napus L.) is a high-quality forage crop with a remarkable nutritional value and productive and fast growth capacity; however, studies on processing methods are limited. This study evaluates the effect of an ensiling process on rape silage quality kinetics, in situ degradability, and milk responses in dairy buffaloes. Firstly, the whole-plant forage rape was ensiled, and silage samples were collected 30, 60, and 90 days after ensiling to determine pH, evaluation of sensory characteristics, and chemical composition. Then, samples were taken for further chemical analysis at days 30, 60, and 90. After that, the degradability of the dry matter (DM) and crude protein (CP) of the silage was evaluated by an in situ degradability experiment using three fistulated buffalos (550 ± 20 kg body weight, 4.7 ± 0.76 years). Finally, whole-plant rape silage (after 60 days) was included in a 10, 20, and 30% of DM dairy buffalo diet in the lactating buffalo ration. The results showed that silage pH did not change significantly during the ensiling process (p > 0.05); however, the silage achieved the optimal comprehensive sensory characteristic score from days 30 to 60. There was also a significant change in neutral detergent fiber (NDF) content and acid detergent fiber content, which decreased significantly (p = 0.001 and p < 0.001, respectively). Ensiling of the whole-plant rape significantly reduced effective DM degradability (p < 0.05) without altering CP degradability (p > 0.05). Furthermore, the inclusion of forage rape silage linearly (p = 0.03) increased milk fat and protein contents and did not affect milk yield, lactose, and urea nitrogen contents in raw buffalo milk. In conclusion, whole-plant rape silage could significantly maintain the optimal ether extract (EE) protein content without affecting CP degradability, in addition to improving milk fat and milk protein. Therefore, ensiling may be an efficient method of forage rape utilization, and forage rape silage can be recommended as a good forage source for dairy buffaloes.